Major exchange rates and value-added exports - Myoung Shik Choi (PSL Quarterly Review, 2021)
This study's primary concern is that exporting or multinational firms tend to be more reliant on intermediate imports with major currencies. We investigate the effects of exchange rates on value-added exports in the linkage with the exports-FDI feedback for sustainable free trade development in OECD countries. Our bilateral findings are that the exchange rate effects are greater for gross than value-added exports except for Germany and greater for intermediate goods than final goods exports except for Italy. But there are no significant differences in the effects of exchange rate changes on exports regardless of US dollar and other currencies. Meanwhile, foreign income has a positive effect on all exports, and the exports-FDI feedback has a weak positive effect on exports to China due to increased FDI into China while the value-added exports-FDI nexus has a weak positive effect on all FDIs.
Keywords: F31; F32; F40; 330; exchange rate; foreign investment; global value chains; value-added exports